Materialistisk kunsthistorie i dag. Benjamin redux: Joselit og Didi-Huberman: Materialistisk kunsthistorie i dag. Benjamin redux: Joselit og Didi-Huberman - Bolt, Mikkel (Periskop – Forum for kunsthistorisk debat, 2022)
ABSTRACT The German avant-garde critic Walter Benjamin remains an important reference within materialist art historical research. His Marxist reading of the emergence of new means of image production as well as his critique of cultural historical artefacts as documents of barbarism continue to inspire scholars and activists, most recently in the toppling of racist statues in 2020. The article discusses the use of Benjamin through a discussion of David Joselit’s After Art and Georges Didi-Huberman’s L’oeil de l’histoire series. Joselit proposes to expand the notion of the artwork through a focus on the networks where images circulate in globalized neo-liberalism but paradoxically ends up with a de-politicized idea of image circulation. Didi-Huberman uses Benjamin in an impressive re-thinking of art history as a question of the apparition and disappearance of images, images as gestures of defiance. Didi-Huberman, however, neglects to connect his analyses of historical images of conflict with the crisis-ridden contemporary historical situation.